Accelerated molecular breeding of novel cytoplasmic male sterility lines in rice using orfH79 or orf290 haplotype. (4th February 2021) - Yanping, Tan; Tong, Chen; Ze, Tian; JiaYang, Li; Xuequn, Liu; Xianying, Tang; Gang, Cheng; Xin, Xu; Chuntai, Wang
Abstract: The identification and development of new cytoplasmic male sterility (CMS) lines in higher plants are important for the preservation of grain security and the prevention of the homogenisation of hybrid rice. Molecular markers‐assisted selection (MAS) based on CMS‐associated genes or mitochondrial‐specific chimeric sequences are important for rapid and effective breeding of new CMS lines and hybrids. In our study, the distribution and allele variation of orfH79 and orf290 genes were characterised from 273 wild and cultivated rice in the AA genome species. Based on the alignment of amino acid sequences, four accessions with orfH79 and three accessions with orf290 were screened. Four novel CMS lines carrying orfH79 haplotypes and three novel CMS lines carrying orf290 haplotypes were then developed using multiple backcross generations with a maintainer line under MAS. The breeding process used in our study provides an efficient and feasible approach for selecting new CMS lines. CMS lines selected in our study are important for enriching rice germplasm resources and guaranteeing rice breeding programmes.